ANALISIS POTENSI KEBANGKRUTAN PERUSAHAAN DENGAN METODE Z-SCORE ALTMAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015) (JURNAL ADMINISTRASI BISNIS, 2016)
ABSTRACT : Maintaining the company's survival in the midst of economic uncertainty andglobal competition is essential. Companies should conduct an analysis of its financial performancein order to still be able to monitor the state of the company to avoid losses even bankruptcy thatthreatens the survival of the company.This research aims to analyze the potential bankruptcy of the company by using Altman’sZ-Score method that specifically demonstrate the potential bankruptcy of the company where thereare three circumstances, those are safe zone, grey zone, and distress zone. The samples aremanufacturing companies listed in Indonesia Stock Exchange during 2013-2015 with samplingpurposive technique.The result showed there are two companies in safe zone, one company in grey zone, 18companies in distress zone, and 10 companies in different zone from year to year.It can be concluded, about 58% of a total sample are in distress zone, so the companieshave to immediately find solution in order to prevent the bankruptcy, like do merger.Key words: Altman Z-Score, bankruptcy, manufacturing